YOUTH POLICY OF THE REPUBLIC OF KAZAKHSTAN - Zhansulu, Makazhanova (European Scientific Journal, ESJ, 2013)
The youth is one of the public and active segments of the population, having important potential weight in the long term. Regularity of modern world development depends on allocation of youth policy in independent activity of the state. "Young professionals have to find the place in processes occurring in the country, take the most active part in future construction" — this phrase from the Addresses of the President of the Republic of Kazakhstan of January 27, 2012, shows the importance of youth and stimulates youth to high achievements in study and work.